Regulation of Migratory Status and Issuance of Nomad Visa in Peru. Positive Impact and Challenges - Cornejo, Daniela (2025)
The advancement of technology and the transformation of work structures toward hybrid and remote models have driven the global rise of the digital nomad lifestyle. In response, various countries have chosen to implement specific migration regulations. In the case of Peru, Legislative Decree No. 1582 regulates the new migratory status of “digital nomad,” aimed at foreign nationals who work remotely using digital tools, provided that their employment relationship is with a company based outside the country.This article introduces the phenomenon of digital nomadism, outlines the profile of the digital nomad, presents a brief comparative study, and based on this, offers an analysis of the positive impact of this migratory category and its main challenges.